Research on the Digital Protection and Inheritance Path of Liao Dynasty Ancient Pagodas - Sun, Qi (Transactions on Social Science, Education and Humanities Research, 2024)
Under the background of the digital intelligence era, this paper discusses the significant importance of the digital protection and inheritance of cultural heritage of ancient pagodas from the Liao Dynasty, expounds the guiding ideology of digital protection and inheritance, and proposes the method of comprehensive utilization of digital technologies such as data collection, database construction, digital modeling, digital maps, and digital museums. These methods aim to promote the digital protection and inheritance of Liao Dynasty ancient pagodas and provide innovative approaches for the dissemination of their history, art, and culture.